Sunday

April 20, 2014

April 20, 2014

Posted by **Confused** on Friday, February 4, 2011 at 3:52pm.

- algebra -
**Reiny**, Friday, February 4, 2011 at 4:50pm2x^2 - 3x + 4 - (3x^2 - x + 2) = 0

-x^2 - 2x + 2 = 0

x^2 + 2x - 2 = 0

I will complete the square, in this case it is easier than using the formul

x^2 + 2x + 1 = 2+1

(x+1)^2 = 3

x+1 = ± ?3

x = -1 ± ?3

**Related Questions**

Intermediate Algebra - Solve using the substitution method. Show your work. If ...

Algebra - (3x+4)/(3x-4)+(3x-4)/(3x+4) --------------------------- Divide top by ...

algebra - simplify (6x^3-16x^2+11x-5)/(3x-2) (3x-2)(2x-1)^2-3 my muliple choice ...

Math - Please show the solutions! 1.) x+y-2(2x-3y) 2.) x+y/2 - 3x-y/4 + x-5y/8 3...

Calculus 12th grade (double check my work please) - 2- given the curve is ...

bobpursley,math - about this problem , I figured it out and i did get the answer...

algebra - I am totally lost on how to solve g(x)=2x^2+3x-1 to find the y and x-...

Algebra 2 - Choose the appropriate simplified expression. 1. 8x^2-10x+3/6x^2+3x-...

Precalculus - Factor completely 2(3x - 5)3(2x + 1)^3 + (3x - 5)^2 (3)(2x + 1)^2...

Pre-calculus - fraction 1) 5/12+7/18-5/6 2) 3x/x-1-1/x=_____/x^2-1x 3) x+1/x^2-...